Comparative Evaluation of Recombinant Human Bone Morphogenetic Protein-2/Hydroxyapatite and Bovine Bone for New Bone Formation in Alveolar Ridge Preservation. Issue 6 (December 2018) - Shim, Jae-Yong; Lee, Youngkyun; Lim, Jae-Hong; Jin, Myoung-Uk; Lee, Jae-Mok; Suh, Jo-Young; Kim, Yong-Gun
Abstract : Purpose: Hydroxyapatite treated with recombinant human bone morphogenetic protein-2/Hydroxyapatite (rhBMP-2/HA) or bovine bone was applied on extraction sockets for alveolar ridge preservation, and the results were compared with respect to clinical and histological bone formation. Materials and Methods: This was a prospective, randomized controlled clinical trial performed on 20 implant placement sites (10 in the experimental and 10 in the control group). rhBMP-2/HA was applied on extraction sockets in the experimental group and bovine bone on those of the control group. The bone at the corresponding sites was biopsied 3 months later, and clinical, histological, and histomorphometric analyses were performed. Results: The alveolar bone height was well preserved in both groups with relatively less change in width in the experimental group compared with the control group. The percentage of new bone was 25.37% ± 17.23% in the experimental group and 6.13% ± 4.32% in the control group; the difference was statistically significant. Conclusions: The alveolar ridge was preserved clinically and histologically in both groups. rhBMP-2/HA resulted in greater new bone formation than bovine bone 3 months after the surgery.